ANALISIS ERGONOMIS PADA ALAT MINI CULTIVATOR PENGOLAH LAHAN PERTANIAN BERDASARKAN METODE NBM DAN OWAS - Muhammad Mahmuda; Sukardi; Wiyogo (Steam Engineering, 2023)
This research aims to: (1) Analyzing the ergonomics of mini cultivator tools based on the Nordic Body Map (NBM) method, and (2) Analyzing the ergonomics of mini cultivator tools based on the Ovako Working Posture Analysis System (OWAS) method. The method in this study was experimental, and the data were analyzed by quantitative descriptive method. The research sample amounted to 5 farmers. The results showed that in the initial posture, namely the upright back position, a score of 1122 category 1 was obtained, which means that the posture is not dangerous and does not need to be improved. In the work posture when running the mini cultivator tool, a score of 2173 category 3 is obtained, which means that the straight work posture must be improved immediately. The results of filling out the NBM questionnaire show that farmers still feel "a little sick" in straight work postures. Meanwhile, the turning posture obtained a score of 4173 category 3 which means that immediate improvement is needed. The results of filling out the NBM questionnaire show that farmers still feel "very sick" in the turning posture. Thus, the mini cultivator tool still needs improvement in several aspects of ergonomics and is discussed in the results of this study